2022
DOI: 10.30736/jt.v13i2.144
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Yogurt Nutrient Content and Antioxidant Activity by Adding Podang Urang Mango Juice (Mangifera Indica L.)

Abstract: Yogurt is a nutrient-rich drink and is mostly liked by many consumers. However, the thermal process in yogurt manufacturing reduces its final product nutrients. Therefore, Podang Urang mango (Mangifera indica l.) juice is added to give the supplementation of the yogurt. This research aims to find out the yogurt nutrient content and antioxidant activity by adding Podang Urang mango juice. There were four different treatments in the process of adding Podang Urang mango juice, there was P0 (0%), P1 (3%), P2 (6%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…LAB is a group of gram-positive bacteria that do not form spores and can ferment carbohydrates to produce lactic acid. However, yoghurt with Podang Urang Mango extracts has fulfilled the quality requirements specified by [Afiyah et al, 2022b] at least 10 7 CFU mL -1 . The amino acids are the building blocks of protein, and their composition is unique for each type of protein.…”
Section: Resultsmentioning
confidence: 99%
“…LAB is a group of gram-positive bacteria that do not form spores and can ferment carbohydrates to produce lactic acid. However, yoghurt with Podang Urang Mango extracts has fulfilled the quality requirements specified by [Afiyah et al, 2022b] at least 10 7 CFU mL -1 . The amino acids are the building blocks of protein, and their composition is unique for each type of protein.…”
Section: Resultsmentioning
confidence: 99%
“…Sodini et al [45] fortified yogurt with commercial whey protein concentrates and found that the fat contents ranged between 2.10% and 3.70%. In one recent study, Afiyah et al [69] found the fat content of control yogurt to be 3.15%. The addition of JSPI in the formulation clearly did not contribute to the increment of fat in the fortified yogurt samples, so the changes are also statistically insignificant.…”
Section: Fat Contentmentioning
confidence: 97%
“…The production was based on Afiyah et al (2022) with some modifications. Briefly, the cow's milk was subjected to heating at 115°C for a duration of 3 min, and subsequently, the temperature was lowered to 40-45°C.…”
Section: Yogurt Productionsmentioning
confidence: 99%